Factors influencing effective implementation of syariah compliance halal food product among SMEs food manufacturers - Abu Karim, Rizuwan; Mohd Nawi, Nolila (Center for Islamic Philanthropy and Social Finance (CIPSF), Universiti Teknologi MARA Melaka, 2017)
Cases of food products with halal certification which are non Shariah compliance as reported by the mass media can lead to the negative perception among Muslim consumer on how halal food production process has been conducted at the food premises. Examining what are the factors that can lead to the effective implementation of Shariah compliance halal food product, this study investigates the influence of halal food supply chain, food safety system and knowledge towards assuring trust attributes of such product. To achieve this objective, primary field data was collected among 200 food manufacturers SMEs which were certified with JAKIM, halal certification. All the respondents are located in Selangor, Kuala Lumpur, Negeri Sembilan, Melaka and Johor Baharu. The findings of this study revealed that halal food supply chain can influence trust. Meanwhile, food safety system and knowledge have no relationship to trust.